Efeitos das externalidades espaciais sobre o crescimento econômico: um ensaio para Alagoas. - Oliveira, Juliana Melo (2010)
For a long time, economists have been interested in understanding what drives economic growth. As a result of that, they have conducted theoretical and empirical studies to explain economic growth differences among countries, regions and cities. In this literature, the idea of geographical space increased the explanatory power of the models by identifying the boundaries of externalities and also by taking into account how distance affects transportation costs. This paper draws on this literature to investigate the existence of spillover effects and how they affect the economic growth of cities in the state of Alagoas. In order to do that, I intend to take into account the centripetal and centrifugal forces that affect externalities and then, access whether or not there is spatial dependence and how this dependence might affect the state economic development.